Dwindling Catla catla population of Gobindsagar reservoir - Kaushal, D K (Indian Journal of Fisheries, 2011)
Fish productivity of a reservoir largelydepends on scientific exploitation andmanagement offish stocks present Therefore,an accurate understanding of the nature andfluctuations in the population of fishes isnecessary for undertaking a fisheries developmentprogramme. The studies on the fisheriesof Gobindsagar reservoir had earlier beendone by Rao and Kaushal (1982) and Kaushaland Tyagi (1988). The present study was doneto examine the causes for the decline of catlafishery vis-a-vis remedial measures for itsrehabilitation in Gobindsagar, a reservoir onthe rivCT Sutlej at latitude 31Â° 25'N and longitude76Â° 25'E.